Characteristics of torrefied empty fruit bunches using microwave heating - Nor Wardah Mohamad Senusi (2017)
In this study, response surface methodology (RSM) based on central composite rotatable design (CCRD) was applied to determine the optimum condition for torrefaction of empty fruit bunch (EFB) using microwave heating process. Three operating variables, namely sample mass (g), sample size (micron) and nitrogen gas flow rate (ml/min). RSM based upon CCRD can be applied to correlate the experimental microwave heating result. The predicted optimum conditions for the torrefaction process was at 15 g for sample mass, 500 micron for sample size and 30 ml/min for nitrogen gas flow rate, resulting in colours of sample, volatile matter content, density, fixed carbon content and moisture content of respectively. Physically, the colours of sample change to the dark brown and blacks after torrefaction process. Based on density values, raw EFB density is 0.265 g/cm3 and torrefied EFB is 0.259 g cm3.Torrefaction process can change the density value of EFB due the mass loss during the process. The moisture content result shows the decreasing values of sample with based on initial mass and final mass. Thus, for maximum production of torrefied can be obtain, with colour changing, low volatile matter content, moisture content and density via microwave heating system can be optimized using RSM.